VD_FINDINFO Arrêt / 2016 / 558 vom 6. Juli 2016 - VD Tribunal cantonal (2016)
ÉVALUATION DE L'INCAPACITÉ DE TRAVAIL, ÉVALUATION DE L'INVALIDITÉ, DEGRÉ DE L'INVALIDITÉ | 28 LAI, 28a al. 1 LAI, 4 al. 1 LAI, 8 LAI, 16 LPGA, 6 LPGA, 7 LPGA, 8 LPGA